2023
DOI: 10.3390/sports11080147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-Myofascial Release of the Lower Back on Myofascial Gliding, Lumbar Flexibility, and Abdominal Trunk Muscle Strength: A Crossover Study

Abstract: Roller massage has been recognized as an effective intervention for managing various conditions. However, data on the effects of roller massage on the dynamic mechanisms of the myofascial and soft tissues of the lower back are limited. This study aimed to examine the effect of the self-myofascial release of the lower back on myofascial gliding, lumbar flexibility, and abdominal trunk muscle strength using a roller massager. This crossover study included 24 college athletes who underwent three interventions—rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Maximum muscle strength can be demonstrated statically and with a high reproducibility, and the measurement is relatively easy [50]. A previous study using this device and using the same procedure showed ICCs 1,3 of 0.975-0.983 (95% CI = 0.952-0.992, p < 0.001) [45]. The participants practiced once or twice under submaximal force, and after sufficient rest, three measurements were taken, with 1 min intervals between each measurement.…”
Section: Measurement Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…Maximum muscle strength can be demonstrated statically and with a high reproducibility, and the measurement is relatively easy [50]. A previous study using this device and using the same procedure showed ICCs 1,3 of 0.975-0.983 (95% CI = 0.952-0.992, p < 0.001) [45]. The participants practiced once or twice under submaximal force, and after sufficient rest, three measurements were taken, with 1 min intervals between each measurement.…”
Section: Measurement Methodsmentioning
confidence: 84%
“…Abdominal trunk muscle strength was evaluated using an abdominal trunk muscle strength measuring device (RECORE @ , Sigmax, Tokyo, Japan) that measures abdominal pressure by wrapping a cuff belt around the abdomen (Figure 2a). After applying approximately 5 kPa of pressure to the abdomen (baseline pressure), the participants were instructed to exert maximum abdominal pressure (peak pressure), and the amount of pressure change (peak pressure-baseline pressure) was defined as the abdominal trunk muscle strength (Figure 2b) [45]. This device assessed the muscle activity of the diaphragm, rectus abdominis, internal oblique, external oblique, transverse abdominis, and pelvic floor muscles [46].…”
Section: Measurement Methodsmentioning
confidence: 99%
“… 26 An ultrasound transducer with a center frequency of 10 MHz (SONIMAGE HS1; Konica Minolta) was used; this transducer provided measurements with an accuracy of less than 0.2 mm, and a single physical therapist conducted all the sonographies. 21 Two examinations were performed on each shoulder, maintaining uniform depth and dynamic range settings for all measurements. To measure humeral head translation, we positioned the ultrasound transducer on the posterior aspect of the shoulder and obtained a long-axis scan of the ISP ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…External APS was provided using an abdominal trunk muscle strength-measuring device (RECORE ® ; Sigmax, Tokyo, Japan), which can be pressurized and decompressed by wrapping a 15 cm-wide cuff belt around the trunk and inflating it using air [44]. Initially, the abdominal pressure of all participants was measured three times while they were in the standing position, and the maximum value was defined as the maximum abdominal pressure (Figure 2).…”
Section: Measurement Methodsmentioning
confidence: 99%